Individual and Contextual Protective and Risk Characteristics for Residents of Recovery Homes. Issue 2 (3rd April 2022) - Jason, Leonard A.; Bobak, Ted; Islam, Mohammed; Guerrero, Mayra; Light, John M.; Stoolmiller, Mike
ABSTRACT: Some recovery homes have facilitating relationships and organizational characteristics, and there are also social capital differences among residents of these recovery homes. It is important to better understand the impact of protective and risk individual and house factors on recovery issues among residents of these community-based settings. Individuals from 42 recovery homes were followed for up to six data collection periods over two years. House level latent class analyses tapped relationship and organizational domains and individual level latent class analyses were from derived from elements of recovery capital. Houses that manifested protective factors provided most residents positive outcomes, except those with elevated self-esteem. Houses that were less facilitating had more negative exits, except for those residents who were the highest functioning. Both individual and house characteristics are of importance in helping to understand risk factors associated with eviction outcomes for residents in recovery homes.